Analyzing Filipinos' Openness to Trade Partnerships and Globalization Using Sentiment Analysis - Francis Mark A. Quimba; Mark Anthony A. Barral (Philippine Institute for Development Studies (PIDS), 2022)
Empirical evidence points to globalization to be favorable for the growth and development of a nation. For the Philippines, trade openness and foreign portfolio helped increase per capita GDP as investment and productivity improve. With trade openness and globalization, nations share and gain access to knowledge and technology, inputs of lower costs, new markets, and talents, which improve domestic economic processes. Over the years, however, skepticism about globalization emerged, which affects governments' foreign strategies and policies and, in turn, the realization of intended benefits. With respect to RCEP, which the country signed in 2020, the Philippines is yet to ratify the deal after clamors to delay or reject the deal. Considering the opposing views, this paper aims to analyze Filipino's openness to globalization and trade partnerships using text mining and sentiment analysis to detect evidence that would suggest prevailing perspective towards these issues. In general, the paper finds favorable sentiments towards globalization and trade openness. This study demonstrates the potential of understanding moods and sentiments towards policy to provide distinctive explanatory power that can be used in harmonizing differences in opinions across several domestic and international issues.
Keywords: 330; globalization; international trade; RCEP; sentiment analysis; trade openness